PENTINGNYA PENDIDIKAN JASMANI BAGI SETIAP PESERTA DIDIK - ., Suharjo (Jurnal Pedagogik Olahraga, 2015)
Abstract Physical education was learning process to move and learning by moving. In addition to study and theacing with the  move for get the purpose learning, in physical education, the student must be move and developing. Developing was through couse purpuse wasn’t aspects of the physical who known is psychomotor, but also developing knowlage and understanding was the ability of cognitive and afective as well as the developing with moving skills, healty and perceptual motors and social emocional. Keywords : Physical Education, Cognitive, Afective and Physicomotor